Does Regulatory Harmonization Increase Bilateral Asset Holdings? - Jonas Vlachos (The Research Institute of Industrial Economics (IUI), 2004)
By combining new data on bilateral asset holdings with data on securities regulation in an empirical gravity model, it is found that bilateral differences in securities regulation lead to decreased portfolio holdings. Hence, regulatory harmonization can foster financial integration. The results are especially strong for equity holdings. It is verified that the results do not just reflect general economic, institutional, and cultural differences. Additional analysis of causality shows the exogenous component of asset holdings to be associated with larger differences in securities regulation. This might suggest that regulatory differences are used to protect domestic capital markets from outside competition.
Keywords: F21; F36; G15; G18; K22; 330; Cross-Border Portfolio Investments; Gravity Model; Harmonization; Home Bias; Integration; Securities Regulation; Wertpapierrecht; Rechtsangleichung; Kapitalanlage